Meriones crassus Sundevall 1842 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Meriones crassus Sundevall, 1842. Svenska Vet. Akad., ser. 3, p. 233. TYPE LOCALITY: Egypt, Sinai, Fount of Moses (Ain Musa), 29° 53' N., 32° 39' E. DISTRIBUTION: N. Africa south to Niger and Sudan; Israel; Jordan; Saudi Arabia; Syria; Iraq; Iran; S. Afghanistan; W. Pakistan. COMMENT: Includes longifrons; see Chaworth-Musters and Ellerman, 1947, Proc. Zool. Soc. Lond., 1947- 1948:482, and Corbet, 1978:127. Formerly included sacramenti and zarudnyi; see Harrison, 1972, The Mammals of Arabia, 3:590, and Lay, 1967, Fieldiana Zool., 54:1 -282. Reviewed by Koffler, 1972, Mamm. Species, 9:1 -4. M. longifrons may be a valid species (DML). ISIS NUMBER: 5301410008092003001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 3), pp. 392-476 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 424, DOI: 10.5281/zenodo.7353031